(3GdQSGdI GdQVGYjIs - (3GdehShj, GdCUagGfj, GdfLaj, GdYGedj, UOQ GdOjf, eMeO Hf UGdM Hf eMeO Hf Rjf GdYGHOjf, J(B1264(3g`s ((3eMeO Ydj Hf eMeO bGSe GdbheTjs)
(3ChdgG (B:s
...(3agPg efXReI aj GdQVGY JYTbgG GdWHGY hdG JeLgG GdCSeGY ChQOJgG aj Vef eG jaJM ebadgG(B...s
(3BNQgG (B:s
(3GdQGHY eG dG jMOK Hg aj GdfcGM MOK GdHJI hgh GdGQJVGY ef CYeGe GdcHQi hCNhGdgG hhVhM gPG GdbSe CZfi Yf GdJfHjg Ydjg aj GdfXe(B. (3JeJ GdcdGe(B...s
(3JHUQI GdYfhGf (B:s
(3efXheI aj GdQVGY eY TQMgGs
(3JHUQI GdeDda (B:s
(3aj GdPQjYI heYLe GdeDdajf Cfg eGJ SfI (B1263(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B164s
Keywords: (3abg GdePGgH GdCNQis